Relationship of Vitamin D Intake with Obesity in Adolescents - Amelia Lorensia; Rivan Virlando Suryadinata; Gesti Nurulalita Arganitya (Global Medical & Health Communication (GMHC), 2022)
Vitamin D deficiency is a problem worldwide, with the primary source of it being sun exposure, which activates the skin's vitamin D substrate. A diet lacking in vitamin D can put people at risk for obesity. The study aimed to determine the relationship between the risk of vitamin D deficiency and obesity in adolescents in Surabaya. It is a case-control research design conducted from March 2018 to January 2019 in a private university in Surabaya, East Java. Respondents were 200 students divided into two groups. The data collection method used the Food Frequency Questionnaire with Spearman correlation analysis to determine the relationship between vitamin D intake and obesity. The results are that the relationship between intake of vitamin D in food and obesity was very strong (0.816). The comparison between the two groups of respondents was 0.666, indicating that the non-obese group had an increased risk of vitamin D deficiency by 0.6 times compared to the obese group. There was a significant relationship between vitamin D intake in food and obesity. It is necessary to investigate further the intake of other foods and the factors that influence obesity in students.